Orphan Lung Diseases 2011
DOI: 10.1183/1025448x.10008410
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteriovenous malformations and other pulmonary aspects of HHT

Abstract: Pulmonary arteriovenous malformations (PAVMs) are vascular structures that provide a direct capillary-free communication between the pulmonary and systemic circulations. The majority of patients have no PAVM-related symptoms, but are at risk of major complications that can be prevented by appropriate interventions. More than 90% of PAVMs occur as part of hereditary haemorrhagic telangiectasia (HHT), the genetic condition most commonly recognised by nosebleeds, anaemia due to chronic haemorrhage, and/or the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 222 publications
(293 reference statements)
0
35
0
Order By: Relevance
“…A Danish epidemiological study demonstrated cerebral abscess rates of 0.4/100,000/yr in the general population but 155/100,000/yr in patients with HHT/PAVMs (38). Crosssectional rates of 7.8 to 19.0% are reported in different series (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)22), including 9.05% in 219 consecutive patients with PAVM/HHT, adjusting for ascertainment bias (22).…”
Section: Concise Clinical Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A Danish epidemiological study demonstrated cerebral abscess rates of 0.4/100,000/yr in the general population but 155/100,000/yr in patients with HHT/PAVMs (38). Crosssectional rates of 7.8 to 19.0% are reported in different series (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)22), including 9.05% in 219 consecutive patients with PAVM/HHT, adjusting for ascertainment bias (22).…”
Section: Concise Clinical Reviewmentioning
confidence: 99%
“…Current international guidelines recommend postembolization CT scans at 6 to 12 months, then every 3 years thereafter, with CT scans every 1 to 5 years for other patients with CTevident PAVMs or positive contrast echocardiographic studies (5). These recommendations were not adopted universally due to radiation concerns (6,7,20,22,88,89), and in the light of data from Reference 13, are likely to be revised in the future. Alternate follow-up strategies used include magnetic resonance imaging, noting resolution is currently limiting (88,89) …”
Section: Radiation Limitation Strategiesmentioning
confidence: 99%
See 3 more Smart Citations